THE FIVE-YEAR PROFESSIONAL ACCOUNTING PROGRAM. - Ashburne, Jim G. (The Accounting Review, 1958)
Abstract The article says that accounting profession includes the practitioner, the accountant in private employment and the accountant who teaches, provided he has measured up to professional standards of proficiency, attitude, and conduct. Thus, the article presents an educational program for communicating to potential accountants the body of professional knowledge and techniques and for instilling in them the attitudes and sense of values found in a professional accountant. It says that the renaissance of the decade is the reaction from overspecialization, the rediscovery that a man with an extremely narrow background of education and experience is at a disadvantage, in many ways, with a competitor having a broader understanding of human experience and culture. The evolution of educational system, however, has set the model of a pyramid, with the early years devoted to the general cultural inheritance, later years to the pursuit of more specialized knowledge in limited areas, and a final topping of concentrated study in a narrow field. Professional training in accounting cannot escape the effects of this pattern. The five-year program described in the article is a first stage program subject to modifications indicated by experience.